Naturalistic exposure to an unknown language alone does not lead to attunement to its phonetic invariants - Georgiou, Georgios P.; Kkese, Elena (My University, 2020)
The present study aims to examine the Cypriot Greek consonant perceptual patterns of Russian speakers who permanently live in Cyprus and do not have experience with Greek, and to determine the effect of naturalistic exposure in an unknown language on speech perception. The experimental group consisted of 16 Russian adult speakers who were living permanently in Cyprus and had no knowledge of Greek, and the control group consisted of 16 Russian adult speakers who were living permanently in Russia, and who did not have knowledge of Greek either. Both populations completed an assimilation test and an AXB discrimination test. The results showed that there were no important differences for the assimilation patterns of both Russian populations, while the discrimination accuracy over Cypriot Greek consonantal contrasts was either similar between the two groups or better for the Russian population living in Russia. Thus, exposure to naturalistic second language stimuli without knowledge of the second language does not contribute to the attunement to phonetic invariants that characterize the second language phones.
La exposición naturalística a un idioma desconocido no conduce por sí sola a la adaptación a sus invariantes fonéticos
Keywords: Consonant perception; Cypriot Greek; Exposure; Russian